2021
DOI: 10.1002/2211-5463.13088
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of galectin‐3 augments the antitumor efficacy of PD‐L1 blockade in non‐small‐cell lung cancer

Abstract: Multiple clinical trials have shown that monoclonal antibodies (mAbs) against programmed death‐ligand 1 (PD‐1/PD‐L1) can benefit patients with lung cancer by increasing their progression‐free survival and overall survival. However, a significant proportion of patients do not respond to anti‐PD‐1/PD‐L1 mAbs. In the present study, we investigated whether galectin (Gal)‐3 inhibitors can enhance the antitumor effect of PD‐L1 blockade. Using the NSCLC‐derived cell line A549, we examined the expression of Gal‐3 in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
(55 reference statements)
1
12
0
Order By: Relevance
“…Each tumor was measured using a dial caliper every two days. Mice (n=10/group; male to female ratio=1:1) were randomly assigned to the following treatment groups: i) mice received 0.2 mg/kg cetuximab (Erbitux ® ; diluted with saline solution; Merck KGaA) once per week via tail vein injection ( 22 ); ii) mice received 10 mg/kg GB1107 (a Gal-3 inhibitor; diluted with PBS; Aobious, Inc.) once per day by oral gavage ( 23 ); and iii) the control group received PBS (100 µl) or IgG (0.2 mg/kg). PBS control was used because GB1107 was dissolved in PBS, while IgG control was used because cetuximab is an antibody to block EGFR.…”
Section: Methodsmentioning
confidence: 99%
“…Each tumor was measured using a dial caliper every two days. Mice (n=10/group; male to female ratio=1:1) were randomly assigned to the following treatment groups: i) mice received 0.2 mg/kg cetuximab (Erbitux ® ; diluted with saline solution; Merck KGaA) once per week via tail vein injection ( 22 ); ii) mice received 10 mg/kg GB1107 (a Gal-3 inhibitor; diluted with PBS; Aobious, Inc.) once per day by oral gavage ( 23 ); and iii) the control group received PBS (100 µl) or IgG (0.2 mg/kg). PBS control was used because GB1107 was dissolved in PBS, while IgG control was used because cetuximab is an antibody to block EGFR.…”
Section: Methodsmentioning
confidence: 99%
“…In this scenario, increasing experimental and clinical evidence indicates that galectins’ blockade as monotherapy does not result in any significant advantage for cancer treatment [ 42 , 110 , 196 , 292 , 312 , 313 ]. However, galectins are involved in patient sensitivity or resistance to chemo-, radio-, immune-, anti-angiogenic, and targeted-therapies (reviewed in [ 314 ]), promising that effective therapeutic avenues can be achieved by combining galectins’ inhibition with the former strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, the accumulation of Tim-3-expressing lymphoid cells and galectin-9-expressing monocytic myeloid-derived suppressor cells positively correlates with resistance to anti-PD1 immunotherapy [ 312 ]. Accordingly, resistance to anti-PD-1 can be overcome by in vitro blockade of the galectin-9/Tim-3 pathway [ 362 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, overall, all of these immune-related functions have provided the rationale for testing whether Gal-3 can potentiate the effect of ICIs. A recent study using belapectin, a polysaccharide polymer that contains galactose and other sugars, has reported that this drug can potentiate the effect of ICIs and anti-OX-40 agonists in preclinical studies of multiple cancer models [ 80 , 81 , 82 ]. Notably, a recent in silico analysis by Takashima and colleagues showed that the genes encoding Gal-3 and Gal-9 were among the top 20 immunotherapy-related genes whose expression was significantly modulated.…”
Section: The Case Of Galectin-3mentioning
confidence: 99%
“…This is the case for GR-MD-02 (also called belapectin), which has shown promising results in a Phase I study with metastatic melanoma and head and neck squamous cell carcinoma [ 80 ]. Another inhibitor of Gal-3, the monosaccharide GB1107, has also been shown to increase the efficacy of anti-PD-L1 to inhibit tumor growth in a mouse xenograft model with the lung adenocarcinoma cell line (A549) [ 82 ]. GB1107 is an inhibitor of Gal-3, with a K d of 37 nM for human galectin-3, suggesting that inhibition of galectins does not require an affinity in the picomolar range.…”
Section: Approaches For Targeting and Delivery Of Galectinsmentioning
confidence: 99%